Contribution of the NH2-terminal EGF-domain of factor IXa to the specificity of intrinsic tenase - Qureshi, Shabir H.; Yang, Likui; Rezaie, Alireza R. (Thrombosis and Haemostasis, 2012)
Factor IXa (FIXa) is a vitamin K-dependent coagulation serine protease which binds to factor VIIIa (FVIIIa) on negatively charged phospholipid vesicles (PCPS) to catalyse the activation of factor X (FX) to factor Xa (FXa) in the intrinsic pathway. Fluorescence resonance energy transfer (FRET) studies have indicated that the Gla-domain-dependent interaction of FIXa and FX with PCPS in the presence of FVIIIa positions the active-site of the protease at an appropriate height above the membrane surface to optimise the catalytic reaction. In this study, we investigated the contribution of the NH2-terminal EGF-domain (EGF1) of FIXa to the recognition specificity of intrinsic tenase by constructing an EGF1 deletion mutant of FIXa (FIXa-desEGF1) and characterising the properties of the mutant in kinetic, direct binding and FRET assays. The results of direct binding and kinetic studies demonstrated that the binding affinity of the mutant for interaction with FVIIIa on PCPS has been impaired greater than 10-fold and the catalytic efficiency of the mutant protease FVIIIa-PCPS complex in the activation of FX has been decreased 100-fold. By contrast, the mutant protease exhibited a normal activity toward FX in the absence of the protein cofactor. FRET measurements revealed that the distance of the active-site of the mutant FIXa relative to PCPS vesicles has been decreased 10 Åfrom 75 ±2 Åfor FIXa to 65 ±2 Åfor FIXa-desEGF1 independent of FVIIIa. These results suggest that the NH2-terminal EGF-domain of FIXa provides a binding-site for FVIIIa and plays an essential spacer function in the intrinsic tenase complex.
Keywords: Factor IXa; factor VIIIa; intrinsic tenase; FRET; Gla-domain; EGF-domains